OBSTACLES AND CHALLENGES OF ISLAMIC BANKING INCLUSION IN BANKING DIGITALIZATION IN THE ERA OF FINANCIAL TECHNOLOGY (FINTECH) - Yusiresita Pajaria (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
This study aims to determine and examine what are the obstacles and challenges of Islamic banking inclusion in banking digitalization in the era of financial technology (FINTECH). The research method used isdata collection method through library research withusing qualitative analysis, meaning describing the processed data in detail into sentences (descriptive). The qualitative analysis carried out starts from empirical analysis, which in its depth is supplemented with normative analysis.To analyze the data, the three data analysis methods used are inductive, deductive, and comparative methods. The results of the study are that the development of Islamic banking has several shortcomings such as: vision, capital, products, financing, human resources (HR), services, information, public understanding; The presence of FINTECH affects Islamic banking, namely by providing contributions such as: easy and cheap services as well as effective and efficient, helping Islamic banks in speed and accuracy in processing business operations data and product marketing, providingsignificant impact on several aspects of the economy, while simultaneously restructuring the face of the Islamic financial industry,rapid development FINTECH directly proportional to the challenges faced,drivers of achieving financial inclusion, the presence of a strong consumer protection system and a digital ecosystem, Islamic banking FINTECH is developing massively in Indonesia, there will be FINTECH and banks collaborating into one.